Avaliação de programas de educação profissional: estudo em organizações do Sistema 'S' - Oliveira, Ilana Maria de (2009)
A throughout the time, the Education focused before in the traditional concepts formation, based on the concepts one in such a way technician, made the positive base for System “S”, whose objective is to form and to characterize the workers in its environment of work, in the attempt to place them to agree again if thus. As propeller of a constructive dialogue to serve of base in the correlation between the theory and the practical one in the analysis process, the evoked theoretical concepts had been the progressive, polytechnical, constructivist, cognitivism, technicality and andragógica, all with its peculiarities, however common in the act to learn and to teach. The methodology of the used research was of four polar regions, whose dissertation establishes a dialogue between four polar regions, namely: Epistemological or historical and philosophical composition of the object of the research, the theoretician whom a dialogue between the authors, the morphologic one promoted, when telling the models of professional education and evaluation, and the technician, which deals with the analyses in the field of the methodology of research and the collected data that had been able to become related during the writings. The first results had been the affirmation of System “S” as development of the workers and, after analysis of the collected data, the affirmations or negations of the hypotheses, being indispensable to observe the traced parallel of the study object.